If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(m + 9) + -4 + 8m = 0 Reorder the terms: 5(9 + m) + -4 + 8m = 0 (9 * 5 + m * 5) + -4 + 8m = 0 (45 + 5m) + -4 + 8m = 0 Reorder the terms: 45 + -4 + 5m + 8m = 0 Combine like terms: 45 + -4 = 41 41 + 5m + 8m = 0 Combine like terms: 5m + 8m = 13m 41 + 13m = 0 Solving 41 + 13m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-41' to each side of the equation. 41 + -41 + 13m = 0 + -41 Combine like terms: 41 + -41 = 0 0 + 13m = 0 + -41 13m = 0 + -41 Combine like terms: 0 + -41 = -41 13m = -41 Divide each side by '13'. m = -3.153846154 Simplifying m = -3.153846154
| -48+12T=16T | | 3=2n-5n | | -15=y+10 | | -1.9+0.45x=0.05-0.3 | | 46+8u=13u-14 | | 3(4x+6)+7x= | | 6x+3=x+11 | | 9c-3(3-c)=4c-17 | | 3x+24=9x | | -x-25=-6x+30 | | x^2+13x+6=0 | | 30p=516 | | x^3-21x+20=0 | | -x+6=8x-3 | | -x-25=-6+30 | | -108=-6n-3(-8n+6) | | -0.10(19)+0.45=0.05(x-6) | | 6(c-7)=-18 | | -15(2x-7)+24=89 | | 3y+4=5y+6 | | 7.7(x-4)=-0.3x+25.2 | | 5[2(3x-3)-4(2x-3)]=3x+17 | | 90=2l+2w | | 4(x-5)+6=2(x-5) | | 5(2x-3)=2(x-2)+5 | | 2X^2-11X-6=0 | | 10y-13=3y+8 | | -3z=12 | | 7(4x+6)=-126 | | 2x*2+21x-11=0 | | f=3x^2-26x+48 | | 8n+5=6n-3 |